Ideologi dan Dakwah dalam Lirik Lir-Ilir: Analisis Wacana Kritis Fairclough - Hidayah, Nailul; Mahliatussikah, Hanik (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2025)
Traditional songs are a form of cultural heritage that carry moral, social, and spiritual messages, while also reflecting the identity of a community. This study aims to analyze the Javanese traditional song Lir-Ilir using the Critical Discourse Analysis (CDA) approach based on Norman Fairclough's model, in order to uncover its symbolic meanings, usage context, and its connection to ideology and social transformation within Javanese society. The song Lir-Ilir, believed to have been created by Sunan Kalijaga, not only functions as a medium for Islamic da'wah (preaching), but also as a tool for character education and the preservation of local culture. This research employs a qualitative method with the primary data source being the lyrics of the song Lir-Ilir in Javanese and its translation. The analysis is conducted through three dimensions: the text dimension, the discourse practice dimension, and the social practice dimension. The findings of this study show that the song contains Sufi symbols and Islamic values such as calls for self-reflection, the enhancement of faith, and the importance of fulfilling religious duties. The lyrics in the song reflect cultural syncretism, as seen in the use of agrarian metaphors such as “tandure wus sumilir” and “penekno blimbing kuwi”, which convey Islamic messages while remaining grounded in Javanese cultural expressions. This illustrates how Islamic values are subtly embedded through local symbols, resulting in a form of acculturation that avoids cultural resistance. To this day, Lir-Ilir remains socially and culturally relevant as a medium for teaching spiritual values and local wisdom, as well as serving as an effective example of how moral messages can be conveyed through art that adapts to the times.